BclI Glucocorticoid Receptor Polymorphism in Relation to Arterial Stiffening and Cardiac Structure and Function: The Hoorn and CODAM Studies. (10th January 2017) - van Moorsel, Dirk; Henry, Ronald M.; Schaper, Nicolaas C.; van Greevenbroek, Marleen M.; van Rossum, Elisabeth F.; 't Hart, Leen M.; Schalkwijk, Casper G.; van der Kallen, Carla J.; Dekker, Jacqueline M.; Stehouwer, Coen D.; Havekes, Bas
Abstract: BACKGROUND: Chronic glucocorticoid excess is associated with arterial stiffening and cardiac dysfunction. The Bcl I glucocorticoid receptor (GR) polymorphism increases GR sensitivity and is associated with a higher body mass index (BMI) and some proxies for cardiovascular disease (CVD). Whether Bcl I influences arterial stiffening and cardiac dysfunction is currently unknown. Therefore, the aim of the present study was to investigate the association of the Bcl I polymorphism with arterial stiffening and cardiac structure and function. METHODS: We conducted an observational cohort study, combining 2 cohort studies designed to investigate genetic and metabolic determinants of CVD. We genotyped 1, 124 individuals (age: 64.7 ± 8.5 years) from the Hoorn study and Cohort on Diabetes and Atherosclerosis Maastricht (CODAM) study for Bcl I. Several arterial stiffening indices of the carotid (Hoorn and CODAM study), brachial and femoral artery and the carotid-femoral pulse wave velocity (Hoorn study only) were determined. In addition, in the Hoorn study, we determined several variables of cardiac structure and function. RESULTS: We identified 155 homozygous carriers (GG), 498 heterozygous carriers (CG), and 471 noncarriers (CC) of the Bcl I polymorphism. Bcl I genotypes did not display significant differences in variables of arterial stiffening (e.g., carotid distensibility coefficient (DC): 12.41 ± 5.37 vs. 12.87 ± 5.55 10 −3 /kPa [mean ± SD]; P = 0.38; homozygous vs. noncarriers). In addition, no clear differences in estimates of cardiac structure and function were found. CONCLUSIONS: Even though Bcl I is associated with a higher BMI and some proxies of CVD, our results do not support the concept that Bcl I carrier status is associated with greater arterial stiffening or cardiac dysfunction.